Pengaruh Model Pembelajaran Problem Posing Terhadap Hasil Belajar Matematika Materi Himpuan Pada Siswa Kelas VII SMP Negeri 11 Kota Tidore Kepulauan - Hujairah Hi. Muhammad (Jurnal Ilmiah Wahana Pendidikan, 2022)
The aims of this study are (1) to determine student learning outcomes using the problem posing learning model, (2) to determine whether there is an effect of problem posing learning models on mathematics learning outcomes for class VII students of SMP Negeri 11 Tidore Islands City in the even semester of the 2021 academic year. /2022, and (3) to find out how much influence the problem posing learning model has on the mathematics learning outcomes of the set material for the seventh grade students of SMP Negeri 11 Tidore Kepulauan City in the even semester of the 2021/2022 academic year. The method used in this research, the research approach used is quantitative research, the type of research used is quasi-experimental research. The sampling technique used is saturated with the same number of population and samples, namely 40 students from class VII A and class VII B and the source of data in this study is primary data, namely students of class VII A and VII B then secondary data derived from the results of the research. observation. The instruments used in this research are observation and post test instruments. The data analysis technique used is the t-test and the procedure in this study through the stages of preparation, submitting permits, preparing instruments and carrying out learning in the control class and experimental class, giving post tests, data collection, data analysis, data interpretation and withdrawal. conclusion. After the researchers conducted research and obtained data, the researchers analyzed the data using the t-test. It can be seen that there are differences in learning outcomes between students who are taught using the problem posing learning model and the conventional learning model with a value (t_count = 3.226> t_table = 2.025) at the rate significant 5%. Thus, it can be concluded that there is an effect of the problem posing learning model on the mathematics learning outcomes of set material in class VII SMP Negeri Tidore Islands in the even semester of the 2021/2022 academic year. The large influence of the proberm posing learning model on the mathematics learning outcomes of set material for class VII students of SMP Negeri 11 Kota Tidore Islands for the 2021/2022 academic year is 18.42%.